THE ROLE OF INTRA-PARTY PRIMARY ELECTIONS IN ZAMBIA’S DEMOCRACY: LESSONS FROM ZAMBEZI WEST CONSTITUENCY (Isagoge - Journal of Humanities and Social Sciences, 2021)
Elections are one sure way people at the grassroots express their choice of who should lead them and discard those they feel do not serve them well. However, elections lose their meaning once a few individuals in the name of political party representatives usurp the power of the people to elect credible leaders. This was a qualitative study conducted to describe the factors that affect the credibility of primary elections using one case of Zambezi West Constituency. Participant observation was a method of collecting data from eleven key informants. An observation and interview guide were used to collect data. Data was recorded on Mp3 sonny recorder, iphone camera and note books. Transcriptions were done and themes identified during analysis. Findings show that generally the primary elections did not reflect the will of the people as the final outcomes were affected by natural and artificial factors. Most importantly, the elections were characterised by lack of transparency, fathergodrism, corruption, lack of planning for different terrains and vested interests by party officials in preferred candidates. It is recommended that community party members should be the ones allowed to vote for their candidates and not party representatives at ward, constituency, district and provincial levels. Primary elections should be well planned in order to gain credence in the electoral process.Key words: Elections, Primary elections, voters, Zambia, Zambezi West, Constituency